Green Intellectual Capital in Emerging Asian Economies: A Systematic Literature Review - Mochtar, Raja Ade Fitrasari; Saputra, Dian (Akuntansi & Ekonomika, 2026)
This study examines Green Intellectual Capital (GIC) in Asia through a Systematic Literature Review (SLR). Articles were collected from the Scopus and Dimensions databases, resulting in 412 initial records. Following PRISMA procedures and MMAT quality assessment, 16 empirical studies were selected for thematic synthesis. The findings show that GIC development in Asia is influenced by institutional pressure, organizational culture, industry characteristics, digital capabilities, and workforce dynamics. Government intervention, leadership commitment, and technological readiness emerge as key drivers of GIC. The review highlights that GIC is a context dependent capability shaped by interactions between external institutional forces and internal organizational resources. These findings provide insights for managers and policymakers in developing sustainability-oriented strategies across Asian economies.